Fabrication of Gold Nanostructures on Quartz Crystal Microbalance Surface Using Nanoimprint Lithography for Sensing Applications - Ryosuke Nishitsuji; Kenji Sueyoshi; Hideaki Hisamoto; Tatsuro Endo (Micromachines, 2022)
A quartz crystal microbalance (QCM) is a sensor that uses the piezoelectric properties of quartz crystals sandwiched between conductive electrodes. Localized surface plasmon resonance (LSPR) is an analytical technique that uses the collective vibration of free electrons on metal surfaces. These measurements are known as analysis techniques that use metal surfaces and have been applied as biosensors because they allow for the label-free monitoring of biomolecular binding reactions. These measurements can be used in combination to analyze the reactions that occur on metal surfaces because different types of information can be obtained from them. However, as different devices are used for these measurements, the results often contain device-to-device errors and are not accurately evaluated. In this study, we directly fabricated gold nanostructures on the surface of a QCM to create a device that can simultaneously measure the mass and refractive index information of the analyte. In addition, the device could be easily fabricated because nanoimprint lithography was used to fabricate gold nanostructures. As a proof of concept, the nanoparticle adsorption on gold nanostructures was evaluated, and it was observed that mass and refractive index information were successfully obtained without device-to-device errors.